EDUCAÇÃO E CINEMA: crítica à domesticação da memória em filmes de animação dos estúdios Disney - Sten, Samira da Costa (2020)
The scope of this thesis is to highlight the pillars of the cultural industry that support the production of the narrative and the type of memory conveyed by the animation films of Disney studios. In addition, it is based on the critical theory of society